Locus of Control and Effectiveness of Bad Loans in Savings and Loan Co-operatives - Antonius Yohanes William Timuneno; Maria Goreti Malut; Selfiana Goetha (LP2M IAIN Palopo, 2026)
This study examines the relationship between locus of control and the effectiveness of minimizing bad debt risk among employees of Savings and Loan Cooperatives in Kupang City. A qualitative descriptive method with a case study approach was used, analyzing and refining informants’ responses to explain causal relationships between variables.Findings reveal the presence of both internal and external locus of control in credit distribution practices at the Swastisari, Adiguna, and Serviam Cooperatives, which served as the research objects. Interpretations of locus of control varied among cooperatives. The results indicate that Swastisari and Adiguna tended to operate with a predominantly external locus of control, while Serviam showed stronger indications of an internal locus of control. Each cooperative applied its own strategies to maintain credit effectiveness. However, the research indicates that effectiveness was closely linked to the locus of control perspective, with indicators such as timeliness and efficiency reflecting this orientation. Variations in implementation outcomes were related to the specific methods employed to achieve performance targets.Overall, the study suggests that these locus of control patterns contribute to relatively low credit risk across all three cooperatives. Nevertheless, significant indications of credit risk were found only in the Serviam Cooperative.